Antimicrobial and antioxidant activities of Flammulina velutipes polysacchrides and polysacchride-iron(III) complex. (1st April 2017) - Dong, Ya-ru; Cheng, Shu-jie; Qi, Guo-hong; Yang, Zhi-ping; Yin, Shi-yu; Chen, Gui-tang
Highlights: Polysacchride-iron complex was prepared with Flammulina velutipes polysaccharide. Antibacterial antifungal and antioxidant activities were investigated. FVP-Fe and FVP2-Fe could significantly suppress the bacteria. FVP-Fe and FVP2-Fe could scavenge superoxide anion radical. FVP and FVP2 exhibited relatively strong antioxidant activity. Abstract: FVP is polysacchrides obtained from Flammulina velutipes . A polysacchride named FVP2 was isolated from FVP by DEAE cellulose-52 chromatography and Sephadex G-100 size-exclusion chromatography. FVP-Fe and FVP2-Fe were synthesized by neutralization of FeCl3 carbohydrate solution. The antibacterial and antifungal activities of FVP, FVP2, FVP-Fe, FVP2-Fe were investigated and their antioxidant effects on hydroxyl, 2, 2-diphenyl-1-picrylhydrazyl (DPPH), superoxide anion, 2, 2′-azobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals, reducing power, inhibition of malondialdehyde (MDA) were assessed in vitro. The results suggested that FVP-Fe and FVP2-Fe significantly suppressed the growth of bacteria Staphylococcus aureus, Escherichia coli, and Bacillus subtilis, and have relatively strong antioxidant activity to scavenge superoxide anion radical. In addition, FVP exhibited strong antioxidant activity to eliminate hydroxyl, DPPH, ABTS radicals, had high reducing power and inhibited the MDA production of health mice liver homogenate induced by auto-oxidation and Fe 2+ -H2 O2 system.